(untitled) (Ukrainian Journal of Ophthalmology, 2026)
An original technique for enucleation of the eyeball with advanced retinoblastoma using high-frequency electric welding of biological tissues (HFEWBT) was developed in SI “Filatov Institute of Eye Diseases and Tissue Therapy of NAMS of Ukraine” in 2013. Purpose. To study in experiment the effect of different modes of electric high-frequency current on structural changes of the rabbit’s optic nerve and the extension of the structural changes after eye enucleation. Material and Methods. 14 Chinchilla rabbits (21 eyes) were enucleated the eyeball using an EK-300M1 unit. We used two modes of the HF-current exposure for transection of the optic nerve: Group 1 (11 eyes), a cutting mode (current intensity, 1.5 A; voltage, 200 V; power, 350 W; frequency, 66 kHz; exposure, up to 3 sec); Group 2 (10 eyes), a welding (current intensity, up to 0.3 A; voltage, 40-60 V; frequency, 66 kHz; exposure, up to 3 sec) + cutting mode. Fragments of the optic nerve excised during the surgery were studied light-optically and ultrastructurally. Results. Using both cutting and welding+cutting modes of the HFEVBT method for the transection of the optic nerve caused the development of dry necrosis in the parenchyma and sheaths of the optic nerve not only in the site of exposure but also at the distance which depended on the mode used. Herewith, the welding+cutting mode caused necrosis, growing by the Day 7 up to 3-4 mm wide, which two times exceeded the necrosis extension when using the cutting mode. Degeneration and gliosis of the optic nerve in Group 2 (welding+cutting) occurred within the greater area than that in Group 1 (cutting), reaching the optic disc and sensory retina. Conclusions. We believe that the extension of the destructive changes when using the welding+cutting HFEWBT mode can increase the ablasticity of enucleation of the eyes with retinoblastoma at high risk of optic nerve invasion.